Pengaruh Suasana Tempat Dan Gaya Hidup Modern Terhadap Keputusan Pembelian Pada Konsumen Coffee Shop: Studi Kasus Pada Etika Coffee - Angelina Virgilia Putri Deo; Yayan Hendayana; Ari Sulistyowati (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
The research article on the Influence of Place Atmosphere and Modern Lifestyle on Purchasing Decisions of Coffee Shop Consumers (Case Study on Coffee Ethics) is research that aims to build a research hypothesis on the influence between variables that will be used in further research. The method of this research article is to use quantitative methods, while the type of research used is descriptive research. The results of this research article are: 1) The influence of atmosphere has a significant influence on purchasing decisions; 2) The influence of modern lifestyle has a significant influence on purchasing decisions; 3) The influence of modern atmosphere and lifestyle has a significant influence on purchasing decisions.